1970
DOI: 10.3126/jnps.v30i1.2457
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Laboratory Profile and Immediate Outcomes of Hyperbilirubinemic Babies Admitted in Kanti Children Hospital

Abstract: Introduction: Jaundice is an important problem in the neonatal period especially in the first week of life. Our objective of the study is to find out the immediate outcome of hyperbilirubinemic babies admitted in Kanti Children Hospital. Methodology: This is a retrospective study and carried out in tertiary care paediatric hospital. Results: Altogether 73 babies were enrolled in the study. Male babies outnumbered the female (72.6% vs. 27.4%).Only 2.4% babies were near-term. LBW babies constitute 19.2% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
2
7
1
Order By: Relevance
“…Among half of the cases (52.4%) range of serum total bilirubun was found between 15 and 19.9 mg/dl. Same results were observed in the study of Nepal D et al 5 . They mentioned that maximum number (67.1%) of infants' peak serum bilirubin fell in the range of 15-19.9 mg/dl.…”
Section: Results and Observationsupporting
confidence: 77%
See 1 more Smart Citation
“…Among half of the cases (52.4%) range of serum total bilirubun was found between 15 and 19.9 mg/dl. Same results were observed in the study of Nepal D et al 5 . They mentioned that maximum number (67.1%) of infants' peak serum bilirubin fell in the range of 15-19.9 mg/dl.…”
Section: Results and Observationsupporting
confidence: 77%
“…Pre-term and low birth weight babies were having higher levels of serum total bilirubin but the difference was not significant (P>0.05) ( In our study out of 63, 40(62%) cases were diagnosed as having physiological jaundice by while others were having ABO incompatibility (15%), Rh incompatibility(8%), septicemia(12%) and G-6 PD deficiency(3%). In the study of Nepal D et al 5 they noted that clinical sepsis as defined by WHO criteria was found in 86.3% of babies. Nearly 1/3rd (32.9%) babies were ABO incompatible and 4.1% babies were Rh incompatible.…”
Section: Results and Observationmentioning
confidence: 99%
“…Among half of cases range of serum total bilirubin was found between 14-18 mg/dl. Same results were observed in the study of Nepal D et al [8] . They mentioned that maximum number of infants' peak total serum bilirubin fall in the range of 15-19.…”
Section: Laboratory Parameterssupporting
confidence: 87%
“…Male newborns had more risk of jaundice, in studies by Mantani et al, Sharma et al and Maisal et al [15][16][17] . The serum bilirubin levels and weight of the newborn had no correlation but in the studies by Nepal D et al (19.2%) and Chaudhary et al (42%) observed significance with weight of the newborn (SGA) [18][19] . The mean age of presentation was 3.74 ± 2.34 days.…”
Section: Discussionmentioning
confidence: 99%